New, mainly southern hemisphere, freshwater families of Amphipoda (Crustacea), together with a description of the first freshwater calliopiid, Lutriwita bradburyi gen. nov. et sp. nov. - Lowry, J. K.; Myers, A. A. (Zootaxa, 2012)
Nine new freshwater amphipod families are described: Chillagoeidae fam. nov.; Crangoweckeliidae fam. nov.;Dussartiellidae fam. nov.; Falklandellidae fam. nov.; Giniphargidae fam. nov.; Pseudingolfiellidae fam. nov.; Sandroidaefam. nov.; Sensonatoridae fam. nov. and Uronyctidae fam. nov. The subfamily Seborgiinae Holsinger, 1980 is raised tofamily level and two families, Austroniphargidae Iannilli, Krapp & Ruffo, 2011 and Pseudoniphargidae Karaman, 1993,are revised. The first freshwater example of the extensive marine family Calliopiidae, Lutriwita bradburyi gen. nov., sp. nov., is described from Australia.